53 Preliminary characterization study of a miniaturized GaN-based X-ray detector for Virtual Fluoroscopy. (December 2018) - Guiral, P.; Pittet, P.; Grondin, Y.; Jalade, P.; Galvan, J-M.; Lu, G-N.; Desbat, L.; Cinquin, P.
Abstract : Introduction: An innovative Virtual Fluoroscopy (VF) concept has recently been introduced to reduce both patient and staff doses in a large proportion (more than 10 times) during image guided catheterization procedures[1] . VF implements i) a rotating collimator enabling a fan beam scanning of the ROI and ii) a miniaturized X-ray detector embedded on the wire guide tip. The synchronized detection of each detector exposure allows the real time localization of the detector, (i.e. of the guide tip which can thus be back projected on the preoperative image for virtual image guidance). The performance of VF in terms of localization accuracy and of dose reduction relies on a large amount on the performances of the X-ray detector. GaN-based detector shows very suitable properties for VF, especially in terms of biocompatibility, miniaturization, response level and speed[2–4] . We present here the preliminary characterization study of a GaN-based detector for such an application. Methods: We have developed an experimental setup for the characterization of the GaN detector probe in static and dynamic (rotating) mini-fluoroscopy beam 2 . The GaN probe consists of a 0.027 mm 3 crystal optically coupled to a 370 μ m optical fiber. Measurements were carried out on a SIEMENS Axiom Luminos dRF operated in automatic pulsed fluoroscopy mode at 15 fps. The testing bench implements a fixed Φ =5 mm circular collimator followed by a rotating collimator for ON/OFF modulation of the irradiation beam (pulse of 1 ms). The static dose rate at the detector probe position was also measured in an open field (with the same irradiation condition) by using a reference detector. Results: The miniaturized GaN based detector allows the detection of the fluoroscopy irradiation within 200 μ s, i.e. for a skin dose 50 times lower than the dose per fluoroscopy frame. It was operational for both static and dynamic (rotating) field conditions. Nevertheless, the detector was not yet synchronized on the rotating collimator for these studies and thus, larger standard deviations were observed on dynamic measurements as compared to the static ones. Conclusions: A GaN based X-ray detector has been characterized in the context of VF. It gives very encouraging results, but some optimizations on detector sensitivity and time resolution remain to be done to reach the optimal performances for VF.